A 10-year retrospective study of methicillin-resistant Staphylococcus aureus from burn wound infection in southeast China from 2013 to 2022 - Gu, Feifei; He, Weiping; Zhu, Dedong; Yang, Peilang; Sun, Jingyong; Han, Lizhong (Frontiers in Microbiology, 2023)
Background: Methicillin-resistant Staphylococcus aureus (MRSA) is one of the most commonly encountered pathogens among burn patients incurring substantial morbidity and mortality. In order to investigate the epidemiology and feature of MRSA in burn wound infections, we conduct a 10-year retrospective study on MRSA isolated from burn patients with burn wound infections from southeast China from 2013 to 2022. Methods: One hundred MRSA isolates (10 isolates each year) from burn wound infection among burn patients from 2013 to 2022 were randomly selected and enrolled. Besides the clinical data of the 100 burn patients, MRSA isolates were characterized by antimicrobial susceptibility testing, detection of toxin genes, and molecular typing. Results: The median time from onset of burns and admission to MRSA detected was 13 and 5 days respectively. No MRSA isolate was found resistant to quinupristin/dalfopristin, linezolid, and vancomycin. Toxin gene seg was found most frequently (90%) followed by sea (70%) and eta (64%). CC8 (74%), ST239 (70%), and SCCmec III (72%) was the most common CC, ST, and SCCmec type, respectively. Conclusion: ST239-III (70%) was the predominant clone found in MRSA from burn wound infection among burn patients in southeast China. ST239-III was less found from 2018 to 2022. A higher diversity of MRSA clones was observed in these recent 5 years than that during 2013 to 2017.